2019
DOI: 10.35310/accruals.v3i2.56
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Profitability, Leverage, Firm Size, Political Connection and Fixed Asset Intensity on Tax Avoidance (Empirical Study on Mining Companies Listed in Indonesia Stock Exchange 2015-2017)

Abstract: The purpose of this reserch is to examine and analyze (1) the influenceof profability on tax avoidance, (2) the influence of leverage on tax avidance, (3) the influence of company size on tax avoidance, (4) the influence of political connection on tax avoidance, and (5) the influence of intensity of fixed assets on tax avoidance The object of this research used mining company listed in BEI in 2015-2017. Companies which used as sample were 17 samples for 3 years of observation. The technique of data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 3 publications
3
10
1
13
Order By: Relevance
“…This research is in line with the results obtained by Putriningsih et al (2018), Angelia and Dwimulyani (2019), Putra and Jati (2018), Oktamawati (2017), Prapitasari and Safrida (2019), and Yulyanah and Kusumastuti (2019) who found that profitability has a positive effect on tax avoidance. Profitability is one of the benchmarks for a company in its ability to earn profits for the company's going concern.…”
Section: Effect Of Profitability On Tax Avoidancesupporting
confidence: 92%
See 2 more Smart Citations
“…This research is in line with the results obtained by Putriningsih et al (2018), Angelia and Dwimulyani (2019), Putra and Jati (2018), Oktamawati (2017), Prapitasari and Safrida (2019), and Yulyanah and Kusumastuti (2019) who found that profitability has a positive effect on tax avoidance. Profitability is one of the benchmarks for a company in its ability to earn profits for the company's going concern.…”
Section: Effect Of Profitability On Tax Avoidancesupporting
confidence: 92%
“…So that profitability becomes an indicator for companies to increase firm value, but a high profit level also causes a large income tax burden. Previous research conducted by Prapitasari and Safrida (2019), Yulyanah and Kusumastuti (2019), and Permata et al (2018) found that profitability has a positive effect on Tax Avoidance. Different results were obtained by Rifai and Atiningsih (2019) and Oktamawati (2017) that profitability has a negative effect on Tax Avoidance.…”
Section: Definition Of Profitabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…Perusahaan yang memiliki kepemilikan aset tetap bukan hanya untuk mengatasi penghindaran pajak melainkan untuk mendukung jalannya operasional dalam sebuah perusahaan. Hasil penelitian ini sejalan dengan hasil penelitian yang dilakukan oleh Oktaviani et al, (2021); Aprilia et al, (2020); Ningsih et al, (2020); Prapitasari (2019); serta Riantami dan Triyanto (2018), menyatakan bahwa, fixed asset intensity tidak berpengaruh terhadap penghindaran pajak.…”
Section: Pembahasan Pengaruh Fixed Asset Intensity Terhadap Penghindaran Pajakunclassified
“…Penelitian terdahulu menyatakan bahwa fixed asset intensity berpengaruh signifikan positif terhadap penghindaran pajak Dharma dan Noviari (2017); Noviyani dan Muid (2019); serta Ramadhan dan Kurnia (2021). Sedangkan penelitian lain menyatakan sebaliknya, bahwa fixed asset intensity tidak berpengaruh terhadap penghindaran pajak Oktaviani et al, (2021); Aprilia et al, (2020); Ningsih et al, (2020); Prapitasari (2019).…”
unclassified